WHAT EXACTLY ARE WE TEACHING IN PHYSICAL EDUCATION- THE CASE OF THE SYLLABUS FOR THE LEARNERS WITH INTELLECTUAL CHALLENGES IN KENYA - Munayi, Simon; Gathoni, Benson (American Journal of Recreation and Sports, 2022)
Purpose: Syllabi provide the guide on what is being taught at schools. In Kenya the main objectives of syllabuses are derived from the national goals of education. This allows for consistence so that a learner from one end of the country is taught the same basic concept as another learner from the different end of the country. It provides the teacher with direction on what should be taught when and how deeply the teacher should cover topics. Is this the case for learners with intellectual disabilities? This study went out to interrogate the syllabus for learners with intellectual disabilities. Methodology: A descriptive research design was used in the study. Out of 44 schools that deal with learners with intellectual disability in Kenya, 35 schools were randomly selected for this study. Four schools were used for the pilot study while 31 were used for the main study. Once the schools were selected, the said questionnaire was administered to the principal of the school and one teacher from the final class who teaches physical education. One of the schools did not have the principal present hence only 30 principals were sampled. Once the questionnaires were filled, date from them was tabulated and analyzed. Findings: It was discovered that 64.58% of the teachers though well trained did choose not to adhere to the syllabus. A look at the syllabus indicated that there were some major anomalies that led to this lack of adherence. The syllabus was created for recreation and leisure yet it is supposed to serve physical education and a host of other issues. The objectives set out for learners with intellectual disability take cognizant that these learners need to provide human capital for the society by being independent. Unique Contribution to Theory, Practice and Policy recommendation: The study recommended that there was need to do basic editing of the document further there is need for the document to be evaluated. The training of the teachers is above average and the fact that they choose not to adhere to the syllabus by choice is an indicator that this curriculum need urgent review to meet the need national goals of education.